Relative sensitivity of hydrodynamic, thermodynamic, and chemical processes for simulating the buoyant multiphase plume and surfacing flows of an oil and gas blowout. (January 2023) - Dissanayake, Anusha L.; Socolofsky, Scott A.; Gros, Jonas; Jun, Inok; Zhao, Lin; Boufadel, Michel C.; Arey, J. Samuel
Abstract: Deepwater hydrocarbon releases experience complex chemical and physical processes. To assess simplifications of these processes on model predictions, we present a sensitivity analysis using simulations for the Deepwater Horizon oil spill. We compare the buoyant multiphase plume metrics (trap height, rise time etc), the hydrocarbon mass flowrates at the near-field plume termination and their mass fractions dissolved in the water column and reaching the water surface. The baseline simulation utilizes a 19-component hydrocarbon model, live-fluid state equations, hydrate dynamics, and heat and mass transfer. Other simulations turn-off each of these processes, with the simplest one using inert oil and methane gas. Plume metrics are the least sensitive to the modeled processes and can be matched by adjusting the release buoyancy flux. The mass flowrate metrics are more sensitive. Both liquid- and gas-phase mass transfer should be modeled for accurate tracking of soluble components (e.g. C 1  −  C 7 hydrocarbons) in the environment. Highlights: Sensitivity analysis simulations for the Deepwater Horizon oil spill sub sea plume Integral multiphase plume model for subsea oil and gas blowouts Simulations for subsea live-fluid releases Chemical and physical processes associated with bubbles and droplets